PENGARUH KUALITAS PELAYANAN DAN PREMI TERHADAP KEPUASAN PESERTA DI BPJS KESEHATAN KANTOR CABANG SIBOLGA - Tambunan, Elisabet; Purba, Mery Lani; Silalahi, Tohonan; Hutagalung, Maria (JURNAL MUTIARA MANAJEMEN, 2025)
The aim of this research is to determine the effect of service quality and premiums on participant satisfaction at the BPJS (Social Security Administration) Health Office, Sibolga Branch. The effects of service quality and premiums are analysed both partially and simultaneously on participant satisfaction. The research method used is quantitative research. Data collection was carried out using questionnaires distributed directly to BPJS Health participants at the Sibolga Branch through a survey technique. The sample in this study consists of 99 BPJS Health participants from the Sibolga Branch. The analysis methods employed include validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing. The results of the study indicate that: (1) the service quality variable has a positive and significant effect on participant satisfaction, with a value of 9.113; (2) the premium variable has a positive and significant effect on participant satisfaction, with a value of 3.629; (3) the service quality and premium variables simultaneously have a positive and significant effect, with a value of 68.931; (4) based on the coefficient of determination (R²), the value is 0.590 or 59%, while the remaining 41% is influenced by other variables not examined in this study, such as location, promotion, and others.